Correction of incomplete cleft palate by u-shaped flap palatoplasty - Saleh Amin (Wolters Kluwer Medknow Publications, 2010)
Objectives: During cleft palate repair, velopharyngeal sphincter reconstruction is still a challenge to plastic surgeons. To improve results of surgical treatment of cleft palate and secondary velopharyngeal incompetence, a carefully designed modified procedure for palatoplasty is presented. Materials and Methods: Thirty patients with incomplete cleft palate corrected by this procedure from April 2003 to October 2007 were included. A u-shaped incision was made in the anterior palate to separate bipedicle flap based on the greater palatine arteries of both sides. After complete dissection of the nasal and palatal mucosa, palatal muscles were carefully dissected from the posterior edge of the bones of the hard palate, wherein the well-mobilised flap receded backward spontaneously and elongated the soft palate. After suturing the nasal mucosa in the midline, the dissected palatal muscles of both sides were sutured together in the anterior third of the soft palate. On suturing the nasal mucosa and the palatal muscles, the soft palate became elongated and the oral mucosa was seen receding backward spontaneously to cover the anterior part of the soft palate. Results: All corrected patients showed good results, with no recurrence, no post-operative fistulae, with accepted speech pattern and no need for further pharyngoplasty. The line of the sutured nasal mucosa and the palatal muscles became covered by the healthy non-sutured oral mucosa and the soft palate became elongated, with narrowing of the vellopharyngeal isthmus after this technique. Conclusion: The designed flap allows covering of sutured nasal mucosa and palatal muscles with a healthy unsutured oral mucosa and elongates the soft palate. Thus, there was no incidence of post-operative fistula and no need for further pharyngoplasties.